Fine‐grained management of cloud‐native applications, based on TOSCA. Issue 5 (13th August 2020) - Bogo, Matteo; Soldani, Jacopo; Neri, Davide; Brogi, Antonio
Abstract : Containers and container‐based orchestrators allow deploying and managing multi‐service applications over cloud platforms, by coupling the lifecycle of each application service to that of its hosting container. In this use case letter, we demonstrate how the OASIS standard TOSCA and Toskose allow overcoming such a coupling by enabling to exploit Docker containers as system containers where to independently deploy and manage application services. More precisely, we show how TOSCA and Toskose enable a fine‐grained, service‐aware management of a third‐party multi‐service application on top of existing Docker‐based container orchestrators (such as Docker Compose and Kubernetes) and independently of whether the application is deployed on premises or on a public cloud (such as MS Azure).